RIASEC Holland's reliability and validity on personality of informatics engineering education students in higher education - Elfi Tasrif (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Holland code is an approach used in psychometrics to see human personality through traits that are arranged in six personality domains which are formed using factor analysis. This study aims to test the reliability and construct validity of the RIASEC Holland instrument, which will later be applied to 178 students of Engineering Education in Indonesia. The method used is confirmatory factor analysis. The results of this study indicate that the prediction of the reliability of the six Indonesian versions of Holland's personality using 178 students shows that Cronbach's alpha is quite large, between 0.601 and 0.699. and the intercorrelation between Holland's Personality proved to have a positive correlation. Construct validity test obtained a fit model where the p value = 0.26972 and RMSEA = 0.02.which shows this model is fit, where the model is said to be fit if the p value > 0.05 and RMSEA < 0.05. This shows that the conformity of the empirical data with the RIASEC typology model which is used as a theoretical concept is at a valid level.